Pengembangan LKPD Berbasis Ensiklopedia dengan Pendekatan Deep learning untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SD: Development of Encyclopedia-Based Student Worksheets with a Deep Learning Approach to Improve Elementary School Students' Critical Thinking Skills - Sariadi Sariadi; Retno Dwi Suyanti; Yusnadi Yusnadi (ITScience (Information Technology and Science), 2026)
The achievement of educational goals in this digital era is greatly influenced by rapid technological development, making critical thinking a fundamental skill for elementary school students. The condition of elementary school students in grade IV at UPT SD Negeri 10 Sidomulio remains relatively low, as the assessment results show that 84% of students still lack complete critical thinking skills. The results of interviews with class teachers show that the LKPD used is still very simple, focuses on routine questions, and does not encourage students to think critically. This study aims to describe the process of developing an encyclopedia-based LKPD using a deep learning approach for science subjects for grade IV students at UPT SD Negeri 10 Sidomulio. This study uses the Research and Development method, with the ADDIE model comprising 5 stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques include observation, interviews, questionnaires, and critical-thinking ability tests. The encyclopedia-based LKPD product meets the criteria for high validity, as indicated by expert assessments. Validation by material experts yielded 100%, media experts 95.48%, language experts 97.78%, and learning practitioners 93.75%, indicating that the developed LKPD is suitable for use in the learning process. The development of encyclopedia-based LKPD using a deep learning approach can provide more interactive, contextual, and enjoyable learning. The encyclopedia-based LKPD, developed with a deep learning approach, is valid, practical, and suitable for learning, and has the potential to improve students' critical thinking skills regarding various forms of matter and their changes.